2001
DOI: 10.1007/s007950170002
|View full text |Cite
|
Sign up to set email alerts
|

Altered gap junction activity in cardiovascular tissues of diabetes

Abstract: Hyperglycemia appears to be an important etiologic factor in the development of micro- and macrovascular complications in diabetic patients. However, its detailed molecular mechanism remains unclear. Among various possible mechanisms, it is widely accepted that high glucose level and a diabetic state induce protein kinase C (PKC) activation in vascular cells in cultured and vascular tissues of diabetic animals. Gap junctions are clusters of membrane channels that permit the intercellular exchange of ions and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 20 publications
4
45
0
Order By: Relevance
“…As the first step, we evaluated whether high glucose affected GMC connexin expression and GJIC activity. The results showed that Cx43 expression and the number of Cx43 gap junctions were significantly downregulated by high glucose, which was consistent with some previous results (8,9,11,32). Cx43 family members degrade rapidly, with half-lives of only 1.5 to 5 h (21), suggesting that the reduction of Cx43 expression could be attributed to decreased transcription and translation of Cx43 gene in high glucose.…”
Section: Discussionsupporting
confidence: 91%
“…As the first step, we evaluated whether high glucose affected GMC connexin expression and GJIC activity. The results showed that Cx43 expression and the number of Cx43 gap junctions were significantly downregulated by high glucose, which was consistent with some previous results (8,9,11,32). Cx43 family members degrade rapidly, with half-lives of only 1.5 to 5 h (21), suggesting that the reduction of Cx43 expression could be attributed to decreased transcription and translation of Cx43 gene in high glucose.…”
Section: Discussionsupporting
confidence: 91%
“…Cell cultures exposed to high glucose levels have been used to study gap junctions and specific connexins in isolation, with results showing attenuation of gap junction activity in bovine aortic endothelial and smooth muscle cells [22,23]. Furthermore, investigations using animal models of type 1 diabetes have shown attenuation of EDHF-mediated responses [24] and gap junction activity in mesenteric [25] arteries from streptozotocin (STZ)-induced diabetic rats.…”
Section: Introductionmentioning
confidence: 99%
“…1). The expression of connexins has been reported to be altered in several animals models of pathologies associated with vascular complications (15), such as hypertension (56,159) and diabetes (95,215), which highlights the importance of the direct cell-to-cell interaction for vascular homeostasis.…”
mentioning
confidence: 99%